1999
DOI: 10.1007/s004300050097
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to a recombinant fragment of the CagA protein of Helicobacter pylori in blood donors and patients with gastric cancer: relation to ABO(H) blood group phenotype, stage of the disease and tumor morphology

Abstract: IgG immune response to CagA was evaluated by enzyme-linked imunosorbent assay (ELISA) using a recombinant fragment of CagA as antigen in 171 patients with gastric cancer and 298 blood donors to determine whether it could be related to the ABO(H) blood group phenotype, stage of cancer or tumor morphology. The CagA-ELISA showed a good specificity (93.5%) and sensitivity (88.5%) as compared with immunoblotting for blot CagA-negative and -positive donors. The Helicobacter pylori seropositive blood group A donors r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition to confirming that individuals with blood group A are at a slightly increased risk of stomach cancer, we have, quite strikingly, also shown that individuals with blood group O have a clearly elevated risk of hospitalization for gastric and duodenal ulcers compared with the other blood groups. Although no definitive conclusions can be drawn from this strictly observational investigation, with no access to data about H. pylori infection, a possible explanation is that these observations may result from different susceptibilities and immunologic responses to such infection (8,15,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to confirming that individuals with blood group A are at a slightly increased risk of stomach cancer, we have, quite strikingly, also shown that individuals with blood group O have a clearly elevated risk of hospitalization for gastric and duodenal ulcers compared with the other blood groups. Although no definitive conclusions can be drawn from this strictly observational investigation, with no access to data about H. pylori infection, a possible explanation is that these observations may result from different susceptibilities and immunologic responses to such infection (8,15,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 97%
“…Some studies included multiple cancer sites, and we analyzed these data separately by site, and the total number of studies by site is 123. Among these studies, we identified 36 studies reported results on gastric cancer (AIRD et al, 1953;AIRD et al, 1954;BILLINGTON, 1956;BUCKWALTER et al, 1958;EISENBERG et al, 1958;MACMAHON et al, 1958;BIRNBAUM et al, 1959;BEASLEY et al, 1960;DOLL et al, 1960;BECKMAN et al, 1961;COTTER et al, 1961;NEWMAN et al, 1961;Hartmann et al, 1964;LISKER et al, 1964;Hoskins et al, 1965;Macafee et al, 1967;Glober et al, 1971;van Wayjen et al, 1973;Newell et al, 1974;Akumabor et al, 1986;Kurtenkov et al, 1995;Klaamas et al, 1999;Su et al, 2001;Kamlesh et al, 2005;El et al, 2007;Edgren et al, 2010;Akhtar et al, 2010;Qiu et al, 2011;Gong et al, 2012;Song et al, 2013), 13 studies on pancreatic cancer (AIRD et al, 1960;Newell et al, 1974;Annese et al, 1990;Wolpin et al, 2009;Greer et al, 2010;Wolpin et al, 2010;Ben et al, 2011;Engin et al, 2012;…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In order to validate our results of gastric cancer, we further performed a meta-analysis to assess these associations (6,(11)(12)(13)(14)(15)(16)(17)(18). A total of 9 studies were included according to the inclusion criteria.…”
Section: Meta-analysismentioning
confidence: 99%